Design, synthesis, and biological evaluation of novel 4-oxobenzo[d]1, 2, 3-triazin-benzylpyridinum derivatives as potent anti-Alzheimer agents. Issue 13 (1st July 2019) - Hosseini, Fahimeh; Ramazani, Ali; Mohammadi-Khanaposhtani, Maryam; Barazandeh Tehrani, Maliheh; Nadri, Hamid; Larijani, Bagher; Mahdavi, Mohammad
Graphical abstract: Abstract: Novel 4-oxobenzo[ d ]1, 2, 3-triazin derivatives bearing pyridinium moiety6a–q were synthesized and screened against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). Most of the synthesized compounds showed good inhibitory activity against AChE. Among the synthesized compounds, the compound6j exhibited the highest AChE inhibitory activity. It should be noted that these compounds displayed low anti-BuChE activity with the exception of the compound6i, as it exhibited BuChE inhibitory activity more than donepezil. The kinetic study of the compound6j revealed that this compound inhibited AChE in a mixed-type inhibition mode. This finding was also confirmed by the docking study. The latter study demonstrated that the compound6j interacted with both the catalytic site and peripheral anionic site of the AChE active site. The compound6j was also observed to have significant neuroprotective activity against H2 O2 -induced PC12 oxidative stress, but low activity against β-secretase.